HemoCue against Coulter LH-750 in the estimation of hemoglobin levels of blood donors in mobile collection settings: a comparative study (Faculty of Medicine Universitas Indonesia, 2018)
Background: The fast and outpatient setting for a determination of the hemoglobin (Hb) level is a well-recognized prerequisite to detect anemia in blood donors. This study aimed to evaluate the performance of the HemoCue methods (HemoCue B-Hb and HemoCue-301) against Coulter LH-750 as a reference method for Hb determination.Methods: This study was an experimental cross-sectional study. It includes 455 blood samples that were collected from volunteer blood donors between January 15, 2010 and February 15, 2011. The performance of the three methods and their comparisons were assessed using the analysis of coefficients of variation (CV), linear regression, and mean difference. Correlation coefficient and Bland–Altman plots were drawn to compare the two HemoCue measurements and the automated cell analyzer against each other and to evaluate their results. The Hb concentrations were compared using the concordance correlation coefficient.Results: The findings exhibited that the CV for the three methods Coulter LH-750, HemoCue B-Hb, and HemoCue-301 were 0.60%, 0.72%, and 0.92%, respectively. A statistically significant difference was observed between the means of the Hb measurements for the three methods (p<0.001). The HemoCue B-Hb and HemoCue-301 methods showed the best agreement, and the Coulter LH-750 method gave a lower Hb value compared with the two HemoCue methods. The results showed a positive correlation of HemoCue Hb results compared with the reference method.Conclusion: All three methods provide a good agreement for Hb determination. The new device HemoCue-301 was found to be more accurate compared with HemoCue B-Hb and Coulter LH-750.